Primary thymic extranodal marginal zone B cell lymphoma as an incidental finding in a Caucasian woman. (3rd September 2015) - Krogh Petersen, Jeanette; Larsen, Thomas Stauffer; Møller, Michael Boe; Stahlberg, Claudia
Abstract : Primary thymic extranodal marginal zone B cell lymphoma (TML) is an extremely rare lymphoma strongly associated with autoimmune disease. We report an exceedingly rare case of TML found in a non-Asian population. TML was found incidentally in a 60-year-old Caucasian woman with a short history of muscle and joint pain. An anterior mediastinal mass was detected by a positron emission tomography-CT (PET-CT) scan and thymectomy was performed. The mass was contained within the thymus with a homogeneous pale cut surface with solid areas. Histologically, the typical morphological and immunophenotypic features of TML were found, with a prominent lymphoid infiltrate comprising of small-to-medium-sized neoplastic lymphocytes, plasmacytic differentiation and a distorted thymic epithelial network. Postoperative follow-up has indicated an associated undifferentiated connective tissue disease (UCTD) with features of systemic lupus erythaematosus.